2019
DOI: 10.3389/fnins.2019.01148
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Kinematic Parameters in Decoding Intended Reaching Movements Using Electroencephalography (EEG)

Abstract: The utility of premovement electroencephalography (EEG) for decoding movement intention during a reaching task has been demonstrated. However, the kind of information the brain represents regarding the intended target during movement preparation remains unknown. In the present study, we investigated which movement parameters (i.e., direction, distance, and positions for reaching) can be decoded in premovement EEG decoding. Eight participants performed 30 types of reaching movements that consisted of 1 of 24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Next, we cannot completely rule out the influence of direction on the decoding before grasping phase, since the position of five devices in our experiment setup was fixed. The study of Kim et al showed that direction and distance had the most contribution to the movement, while there was no significant difference observed for position (Kim et al, 2019 ). In our experiment, five devices were arranged in a fan shape to ensure equal distance.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we cannot completely rule out the influence of direction on the decoding before grasping phase, since the position of five devices in our experiment setup was fixed. The study of Kim et al showed that direction and distance had the most contribution to the movement, while there was no significant difference observed for position (Kim et al, 2019 ). In our experiment, five devices were arranged in a fan shape to ensure equal distance.…”
Section: Discussionmentioning
confidence: 99%
“…is can be used to construct intelligent BMI systems to update a decoder online when a BMI system experiences an error. So far, feedforward control has been employed in a BMI system that decodes neural signals to use them as an input command and obtain movement parameters [44]. When a BMI system works well and a user wants to move, feedforward control is sufficient; however, when the system experiences an error because it does not perceive correct user intention, a feedback controller is needed to perform calculations and correct for the delay.…”
Section: Discussionmentioning
confidence: 99%